Public Openness Services in the Framework of Bureaucratic Democratization in the Metro City of Lampung Province - Ratna Wati; Wahyu Tri Putranto (PT Publikasiku Academic Solution, 2023)
This article aims to explain the implementation of bureaucratic democratization in Metro City, especially in public information disclosure services. The background to this writing is that the implementation of public information disclosure is still low in accordance with the mandate of Law Number 14 of 2008 at the Regional Government level. One of them is the Metro City Government which only issued a guardian in 2016 which was previously required 2 years after it was stipulated, namely in 2010. This research was conducted using a mixed method by simultaneously carrying out qualitative methods and quantitative methods with a focus on understanding the apparatus, provision of facilities, and commitment of the Guardian. Metro City in openness of public information. The research used interviews, survey, observation, and document study methods to collect data. This research finds that bureaucratic democratization in public information disclosure services in the Metro City government is already underway, although not yet optimal. This is because the knowledge and understanding of the bureaucratic apparatus still do not fully understand Law Number 14 of 2008 and the contents contained in it. The provision of public services in the form of the formation of PPIDs in each Regional Apparatus Organization (OPD) has still not reached 50%, namely only 36%, and the Metro Mayor's commitment is not yet complete, this is indicated by the slow issuance of Perwali and the low trust of OPD representation in this commitment.